Multimodal cell-cell communication driving CD8+ T cell dysfunction and immune evasion - Chen, Liping; Huang, Qianping; Zhou, Peipei (Frontiers in Immunology, 2025)
Effective anti-tumor immunity critically depends on functional CD8+ T cells, yet in almost all solid tumors, these cells become dysfunctional, exhausted, or spatially excluded. This breakdown of immune surveillance arises not only from cell-intrinsic T cell exhaustion but also from multimodal communication among tumor, stromal, and immune cells within the tumor microenvironment (TME). This communication is mediated not only through direct receptor-ligand interactions but also through a suite of indirect mechanisms, such as metabolic competition, secretion of immunosuppressive metabolites and cytokines, extracellular vesicle exchange, and even mitochondrial transfer via tunneling nanotubes or membrane transfer through T cell trogocytosis. Together, these suppressive interactions impair CD8+ T cell metabolism, effector function, and persistence, thereby enabling tumor immune evasion. In this review, we summarize current understanding of how multimodal cell-cell communication, including immune checkpoints, metabolic reprogramming, and stromal crosstalk, cooperatively drive CD8+ T cell dysfunction. We also highlight emerging therapeutic strategies aimed at rewiring these suppressive networks, with emphasis on translational potential. A deeper understanding of the spatial, molecular, and metabolic context of CD8+ T cell suppression offers new avenues to enhance the efficacy of cancer immunotherapies.